Holocene ice-wedge polygon development in northern Yukon permafrost peatlands (Canada). (1st September 2016) - Fritz, Michael; Wolter, Juliane; Rudaya, Natalia; Palagushkina, Olga; Nazarova, Larisa; Obu, Jaroslav; Rethemeyer, Janet; Lantuit, Hugues; Wetterich, Sebastian
Abstract: Ice-wedge polygon (IWP) peatlands in the Arctic and Subarctic are extremely vulnerable to climatic and environmental change. We present the results of a multidisciplinary paleoenvironmental study on IWPs in the northern Yukon, Canada. High-resolution laboratory analyses were carried out on a permafrost core and the overlying seasonally thawed (active) layer, from an IWP located in a drained lake basin on Herschel Island. In relation to 14 Accelerator Mass Spectrometry (AMS) radiocarbon dates spanning the last 5000 years, we report sedimentary data including grain size distribution and biogeochemical parameters (organic carbon, nitrogen, C/N ratio, δ 13 C), stable water isotopes (δ 18 O, δD), as well as fossil pollen, plant macrofossil and diatom assemblages. Three sediment units (SUs) correspond to the main stages of deposition (1) in a thermokarst lake (SU1: 4950 to 3950 cal yrs BP), (2) during transition from lacustrine to palustrine conditions after lake drainage (SU2: 3950 to 3120 cal yrs BP), and (3) in palustrine conditions of the IWP field that developed after drainage (SU3: 3120 cal yrs BP to 2012 CE). The lacustrine phase (pre 3950 cal yrs BP) is characterized by planktonic-benthic and pioneer diatom species indicating circumneutral waters, and very few plant macrofossils. The pollen record has captured a regional signal of relatively stable vegetation composition and climate for the lacustrine stage of the record until 3950 cal yrs BP. Palustrine conditions with benthic and acidophilic diatom species characterize the peaty shallow-water environments of the low-centered IWP. The transition from lacustrine to palustrine conditions was accompanied by acidification and rapid revegetation of the lake bottom within about 100 years. Since the palustrine phase we consider the pollen record as a local vegetation proxy dominated by the plant communities growing in the IWP. Ice-wedge cracking in water-saturated sediments started immediately after lake drainage at about 3950 cal yrs BP and led to the formation of an IWP mire. Permafrost aggradation through downward closed-system freezing of the lake talik is indicated by the stable water isotope record. The originally submerged IWP center underwent gradual drying during the past 2000 years. This study highlights the sensitivity of permafrost landscapes to climate and environmental change throughout the Holocene. Highlights: Stages: 1) Thermokarst lake, 2) Lake drainage, 3) Wetland, 4) Ice-wedge-polygon mire. Non-climate factors very important for IWP formation, development and degradation. Phases of IWP development and degradation follow general climate pattern in N-Yukon. Independent proxies from pollen, diatoms, macrofossils support reconstruction. Refreezing of talik from thermokarst lake under closed-system conditions.